Examining the Relationship Between Campus Leadership and Institutional Performance in Higher Education Institutions in Sulu - Sophia Punding Danial – Sahial (Future Science / FSH-PH Publications, 2026)
This research aimed to determine the association between campus leadership and institutional performance of higher educational institutions (HEIs) in Sulu. In particular, it investigated the influences of leadership behavior, cultural context, resource availability training and development, community engagement, political support and administrative support as important determinants of faculty and student outcomes. Building on Transformational Leadership Theory and Institution Theory, this study focused on leaders’ dual role in motivating internal actors and purposefully reacting to external institutional mandates. A quantitative research design using a self-made survey questionnaire was used in this study to collect the data from 209 respondents; faculty, administrators and students of five HEIs in Sulu, specifically: Mindanao State University – Sulu (MSU-Sulu), Notre Dame of Jolo College (NDJC), Sulu State College (SSC), Hadji Butu School of Arts and Trade (HBSAT) and Sulu College of Technology Inc. (SCT). All the data collection was made by stratified random sampling. Results were expressed by means of descriptive statistics, t-test and post-hoc analysis, ANOVA and Pearson's correlation coefficient. Results indicated that leadership on campus in Sulu is mainly strong, healthy with clear vision to communicate effectively, and provide solid support for faculty and students. Overall level of faculty satisfaction and productivity and student engagement or learning outcomes were rated high, suggesting an effective influence of leadership on organizational performance. There were highly statistically significant relationships between the leadership factors and faculty and student outcomes.